Efeito da colimação do campo na dose ocupacional e de pacientes nos exames contrastados de videofluoroscopia da deglutição - Ferreira, Karin Cristiane (2024)
The videofluoroscopic swallowing study is a diagnostic procedure that employs ionizing radiation to evaluate the anatomy and physiology of swallowing in real time, and it is essential for investigating swallowing disorders. Despite its clinical relevance, exposure to ionizing radiation requires the application of radiological protection measures to minimize risks for both patients and healthcare professionals involved in the procedure. In discussions of radiological protection issues in fluoroscopy and radiography, the size of the radiation field is generally mentioned in connection with the unnecessary irradiation of parts of the patient’s body that do not need to be visualized. However, excessive expansion of the field size also leads to other effects, such as the excessive irradiation of professionals in the room and changes in the dose rate at the entrance of the patient’s body due to automatic brightness control. The aim of this research is to analyze the results of an experimental study on the dependence of these effects on the irradiation field size and the primary X-ray spectrum. Measurements were carried out under conditions similar to those of actual exams. To simulate the patient’s body, five acrylic plates measuring 30 cm in height, 30 cm in length, and 3 cm in thickness each were used, totaling 15 cm in thickness. The X2 RF sensor (RAYSAFE) was used to measure the dose rate at the entrance and exit surfaces of the simulator, and the specific model used to measure leakage and scatter, the X2 Survey sensor (RAYSAFE), was used to measure the occupational dose rate. The occupational dose rate detector was positioned in the location where the assistant typically supports the patient’s head and/or administers the contrast. The results show that, in radiographic mode, the dose rate at the exit surface of the patient’s body increases with the expansion of the field size, with an increase of up to 85%. The increase in occupational dose rate in radiographic mode reaches 850% and is linearly proportional to the field area. In fluoroscopic mode, the dose rate at the entrance of the patient’s body decreases proportionally with the increase in field size due to automatic brightness control, with this effect reaching 25% with a grid and 50% without a grid.